Cytological Findings in Testicular FNAC in Azoospermia Patient: A Study of 395 Cases - Islam, Md Saiful; Dutta, Papri; Dey, Nishith Ranjan; Kabir, Meherun (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: In the age of assisted reproduction, search for the cause of male infertility is increasing in numbers. As finding of obstructive azoospermia give the male a hope there are increased requisition to the cytopathologist to evaluate the spermatogenesis status of a male. The aim of the study was to see the cytomorphological pattern in azoospermia patients and to determine the procedure's safety. Materials and methods: From January 2015 to June 2022, in Chattogram, Bangladesh, 395 patients with azoospermia were taken in this descriptive study. After all aseptic precautions and local anesthetization aspiration was done from both testes. Cytomorphological analysis was done in the following classes i) Positive for spermatogenesis ii) Hypo-spermatogenesis iii) Early maturation arrest iv) Late maturation arrest v) Sertoli cell only vi) Atrophic. Results: Cytological diagnosis yielded 161 (40.76%) positive for spermatogenesis, indicating obstructive azoospermia, seconded by 'Sertoli cell only' in 115 (29.11%) patients. Both conditions were highest in the age group of 31-40, 93(57.76%) and 72 (62.6%). Hematoma was seen in 04(1.01%) cases and extended period of pain was experienced by 05 (1.26%) patients. Conclusion: FNA of the testis is a much simpler and easily accessible procedure to assess the spermatogenesis status of an azoospermia patient. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 53-56